Analisis Implementatasi Strategi Bauran Pemasaran 7P Pada Usaha Bakso Wong Jowo By Tiwi - Pratiwie Nirmala Dewi; Chandra Hendriyani; Rommy Mochammad Ramdhani (JIP ( Jurnal Industri dan Perkotaan ), 2021)
Abstract: The purpose of this research is to study how the implementation of the marketing mix strategy in the Bakso Wong Jowo By Tiwi business. The current global pandemic, namely Coronavirus Disease (Covid-19), hampers all community activities. The social distancing system that is implemented to minimize the spread of virus transmission, on the other hand has a negative impact. One of the elements most affected by the social distancing system is the labor. Many workers who are dismissed are even laid off (Termination of Employment) due to decreased company activities. Cause of that, the community is expected to be more creative and innovative person in order to survive in fulfilling their daily needs, especially in this pandemic era. One of the ways is making UKM (Usaha Kecil Menengah) which can be done at home by utilizing existing technology. Bakso is a typical Indonesian culinary delicacy that is very much in demand by the public, especially in Cimahi City. Bakso Wong Jowo By Tiwi is a type of UKM that is engaged in home-made culinary (Homemade) with the Javanese slogan "Juara Panganan Ing Omah" which means "Home food champion". However, the large number of competitors and the current pandemic make the Bakso Wong Jowo By Tiwi business must have a good and mature marketing strategy, namely the 7P Marketing Mix strategy. The research method that the author uses is phenomenology with a qualitative approach. The data collection technique was carried out by observation and documentation related to the research. The results showed that the application of the 7P marketing mix method can provide development in the business run by UMKM Bakso Wong Jowo By Tiwi.